Future Direction of Teaching and Learning Module in Nepal - Rai, Man Kumar (Dristikon: A Multidisciplinary Journal, 2024)
This paper studies shift of physical class adopting Information and Communication Technology in teaching and learning activities in Nepal. Integration of ICT in academic activities changes the traditional teaching model ignoring teacher centered method into effective student centered method. The qualitative research employed semi-structured online interviews with secondary students, teachers and parents through Facebook messenger, telephone call, personal interview and Zoom class observation. Documentary analysis provided a ground for the analysis of data gathered through interviews and observations. This paper reports on how online mode of learning would be effective pointing out collaborating learning environment, easy access to materials and in terms of time saving. Moreover, use of ICT in academic activities changes teacher-centered teaching and learning environment into student-centered environment. ICT skills of teachers, poor ICT infrastructure and government policies have been pointed out as hurdles for virtual classes. However, integration of ICT in academic activities is demand of the time. Findings suggest that the use of ICT in academic activities will be effective way of teaching and learning activities in future in Nepal. Moreover, online classes can benefit students who are from marginalized, disadvantaged communities and who have no easy access to schools.